Cassava Starch Inclusion Complexes with Hydrophobic Drugs - ANGGRAENI PUTRI PERDANI (NIM : 10512087), DIAN
The ability of starch in forming complexes with hydrophobic molecules can be applied as drug-carrying molecules, such as papaverine and paracetamol drugs. Papaverine is a type of antispasmodic drug used to improve blood flow in the body. Paracetamol is an analgesic and antipyretic agent used to reduce mild to moderate pain such as headache, migraine and postpartum pain. The main problem in papaverine and paracetamol drug formulations, it has low solubility in water. The solubility of paracetamol in water 14 mg/mL while the solubility of papaverine 25 mg/mL. In starch inclusion complexes, papaverine and paracetamol are wrapped by a single helix of amylose contained in starch. With these characteristics, it is expected that inclusion complexes between starch with papaverine and starch with paracetamol can be formed and can be prepared into tablets. The inclusion complex was prepared by mixing a 1% (w/v) starch solution with each papaverine and paracetamol were varied between 10-50% (based on the weight of starch) at 80-85 oC. In addition, variations in complexing time are also made between 1-5 hours. The results of the starch inclusion complex were characterized using FTIR, XRD, SEM and TGA. The characterization results with FTIR indicate a presence of about 3500-3000 cm-1 (hydroxyl group), 2900-2800 cm-1 (alkane group), 1700-1600 cm-1 (carbonyl group). XRD analysis for starch-papaverine complex results showed the formation of a new peak at 2θ1 = 18,8-20o and 2θ2 = 31,5-33o, while starch-paracetamol complex results showed the formation of a new peak at 2θ1 = 18,2-20,5o dan 2θ2 = 31-32o. Characterization with TGA showed that the starch-paracetamol complex was degraded at 270 oC while the starch-papaverine complex began to thermally degrade at 250 oC. In starch degradation test, the value of α-amylase enzyme activity degrading starch is greater then the activity of α-amylase enzyme when it degrading the product of inclusion complex that is formed.